How university governance affects education service quality: insights from Ethiopian public universities - Atanaw, Bekele; Estifanos, Ashebir Bezabih; Negash, Habtamu Gezahegn (Frontiers in Education, 2025)
University governance plays a significant role in bringing about change because it is one of the most critical variables in determining the success of higher education institutions. Hence, this study aimed to investigate the influence of university governance on the education service quality of Ethiopian public universities. Accordingly, the current study focuses on five key university governance principles: accountability, autonomy, academic freedom, transparency and responsibility. The study utilized a multiple linear regression model, which made use of quantitative data sources. Data was collected from 378 instructors and academic officials from six public institutions, including department heads, deans, faculty heads, and directors. The research utilized a closed-ended questionnaire. Using SPSS software version 20, the quantitative data were examined using the descriptive statistics and inferential statistics techniques. The results of the regression analysis and correlation were discovered. The correlation result indicates that accountability and academic freedom parameters had a positive and strong correlation with education service quality. The regression results showed that academic freedom positively affected the education service quality while accountability and responsibility negatively affected the quality of education services of Ethiopian public universities. Academic leaders and staff of public universities should therefore practice academic freedom, transparency, and autonomous decision-making through implementing university governance principles in their respective public universities in Ethiopia.